Lack of FTSH4 Protease Affects Protein Carbonylation, Mitochondrial Morphology, and Phospholipid Content in Mitochondria of Arabidopsis: New Insights into a Complex Interplay. Issue 4 (13th June 2016) - Smakowska, Elwira; Skibior-Blaszczyk, Renata; Czarna, Malgorzata; Kolodziejczak, Marta; Kwasniak-Owczarek, Malgorzata; Parys, Katarzyna; Funk, Christiane; Janska, Hanna
Abstract : Plants devoid of FTSH4, one of the ATP-dependent metalloproteases in mitochondria, reveal an increased number of abnormal mitochondria, decreased respiratory complexes, and lower amounts of cardiolipins, which is suggested to cause the observed accumulation of oxidative damage. Abstract: FTSH4 is one of the inner membrane-embedded ATP-dependent metalloproteases in mitochondria of Arabidopsis ( Arabidopsis thaliana ). In mutants impaired to express FTSH4, carbonylated proteins accumulated and leaf morphology was altered when grown under a short-day photoperiod, at 22°C, and a long-day photoperiod, at 30°C. To provide better insight into the function of FTSH4, we compared the mitochondrial proteomes and oxyproteomes of two ftsh4 mutants and wild-type plants grown under conditions inducing the phenotypic alterations. Numerous proteins from various submitochondrial compartments were observed to be carbonylated in the ftsh4 mutants, indicating a widespread oxidative stress. One of the reasons for the accumulation of carbonylated proteins in ftsh4 was the limited ATP-dependent proteolytic capacity of ftsh4 mitochondria, arising from insufficient ATP amount, probably as a result of an impaired oxidative phosphorylation (OXPHOS ), especially complex V. In ftsh4, we further observed giant, spherical mitochondria coexisting among normal ones. Both effects, the increased number of abnormal mitochondria and the decreased stability/activity of the OXPHOS complexes, were probably caused by the lower amount of the mitochondrial membrane phospholipid cardiolipin. We postulate that the reduced cardiolipin content in ftsh4 mitochondria leads to perturbations within the OXPHOS complexes, generating more reactive oxygen species and less ATP, and to the deregulation of mitochondrial dynamics, causing in consequence the accumulation of oxidative damage.